2015
DOI: 10.1186/s12889-015-1826-y
|View full text |Cite
|
Sign up to set email alerts
|

Developing the Moti-4 intervention, assessing its feasibility and pilot testing its effectiveness

Abstract: BackgroundThe Moti-4 intervention was developed to prevent addiction and other health problems among vulnerable adolescent cannabis users. The aims of Moti-4 are to reduce the use of cannabis among adolescents and to encourage their motivation to change their behavior.MethodsIntervention Mapping, a systematic approach to developing theory- and evidence-based interventions, was used to develop a protocol for the intervention. The process of developing the intervention also used the method of responsive evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…These trained professionals then recruited participants (N = 31), which were referred by their parents, by agencies for youth care and drop-out, field workers and by student counselors. A pilot study was undertaken with pre-and post-test assessments (Dupont et al, 2015). The results of our pilot study showed that after the intervention, the average weekly amount of money spent on cannabis had decreased by 47%.…”
Section: Feasibility Study Training and Pilot Studymentioning
confidence: 98%
See 4 more Smart Citations
“…These trained professionals then recruited participants (N = 31), which were referred by their parents, by agencies for youth care and drop-out, field workers and by student counselors. A pilot study was undertaken with pre-and post-test assessments (Dupont et al, 2015). The results of our pilot study showed that after the intervention, the average weekly amount of money spent on cannabis had decreased by 47%.…”
Section: Feasibility Study Training and Pilot Studymentioning
confidence: 98%
“…Since 1995, various kinds of targeted prevention initiatives have been applied in the Netherlands including Hasj en weedweek, CIA, Wietcheck and ABC-gesprek (Spits et al, 2014). In the Moti-4 intervention, the most effective elements of these best practices, such as motivational interviewing, self-monitoring, and strengthening behavioral control, were used, mixed and compressed into a protocol (Dupont et al, 2015). The goals of Moti-4 are to reduce the use of cannabis in the target group and to increase their motivation to change their behavior.…”
Section: Moti-4mentioning
confidence: 99%
See 3 more Smart Citations